2022
DOI: 10.1021/acs.nanolett.1c04676
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Superhydrophilicity of Gd-Doped TiO2 Ellipsoidal Nanoparticles Boosts T1 Contrast Enhancement for Magnetic Resonance Imaging

Abstract: The unsatisfactory performance of current gadolinium chelate based T 1 contrast agents (CAs) for magnetic resonance imaging (MRI) stimulates the search for better alternatives. Herein, we report a new strategy to substantially improve the capacity of nanoparticle-based T 1 CAs by exploiting the photoinduced superhydrophilic assistance (PISA) effect. As a proof of concept, we synthesized citrate-coated Gd-doped TiO2 ellipsoidal nanoparticles (GdTi-SC NPs), whose r 1 increases significantly upon UV irradiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The vascular stenosis model was constructed on the left lower limb of SD rats using a retaining clip. ,, After clamping for 10 min, T 1 images of the lower limb blood vessel of SD rats were acquired after intravenous injection of P4-Gd at a dose of 0.05 mmol Gd/kg BW.…”
Section: Methodsmentioning
confidence: 99%
“…The vascular stenosis model was constructed on the left lower limb of SD rats using a retaining clip. ,, After clamping for 10 min, T 1 images of the lower limb blood vessel of SD rats were acquired after intravenous injection of P4-Gd at a dose of 0.05 mmol Gd/kg BW.…”
Section: Methodsmentioning
confidence: 99%
“…In another research, Liu et al synthesized citrate-coated Gd-doped TiO 2 ellipsoidal nanoparticles (GdTi-SC NPs) to improve the efficiency of gadolinium-based T1 contrast agents (CAs) for magnetic resonance imaging (MRI). 124 The in vivo MRI tests on rats demonstrated that the modified TiO 2 NPs have a high potential ability as high-performance T1 contrast agents for the sensitive imaging of blood vessels and the accurate diagnosis of vascular lesions. Peper et al studied redox reactions of aqueous colloidal solutions of both citrate capped- and uncapped-TiO 2 NPs (c-TiO 2 and uc-TiO 2 ) and reported the different redox behaviors of these two systems.…”
Section: Surface Modification Of Tio2npsmentioning
confidence: 98%
“…8 Gadolinium(III) (Gd(III)) has a high magnetic moment and long electron spin relaxation time, and has become the most widely studied magnetic metal center for T 1 -MR imaging applications. [9][10][11] Other metal ion-based agents, such as manganese(II) (Mn(II)) and copper(II) (Cu(II)), are becoming promising candidates for clinical T 1 -MRI practice. [12][13][14] To improve MR imaging contrast, recent investigations have focused on embedding paramagnetic species (such as Gd(III), Mn(II), and Cu(II)) inside iron oxide (IO) nanoparticles to enable the spin of T 1 contrast species to coordinate the local magnetic field induced by the T 2 -weighted IO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%